2008
DOI: 10.1007/s10570-008-9271-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-reinforced composites obtained by the partial oxypropylation of cellulose fibers. 2. Effect of catalyst on the mechanical and dynamic mechanical properties

Abstract: This work describes the partial oxypropylation of filter paper cellulose fibers, employing two different basic catalyst, viz., potassium hydroxide and 1,4-diazabicyclo [2.2.2] octane, to activate the hydroxyl groups of the polysaccharide and thus provide the anionic initiation sites for the ''graftingfrom'' polymerization of propylene oxide. The success of this chemical modification was assessed by FTIR spectroscopy, X-ray diffraction, scanning electron microscopy, differential scanning calorimetry, thermograv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
0
8
0
3
Order By: Relevance
“…The concept of all-cellulose composites has been explored for a wide range of cellulose materials including wood pulp fibres [250,251], filter and Kraft paper [252][253][254][255], MCC [256][257][258][259][260], sisal [261,262], ramie [263], regenerated cellulose (Lyocell) and cellulose fibres spun from an anisotropic phosphoric acid solution (Bocell) [264], and BC [265]. These studies showed great promise.…”
Section: Applications and New Advances In Cellulose Nanocompositesmentioning
confidence: 99%
“…The concept of all-cellulose composites has been explored for a wide range of cellulose materials including wood pulp fibres [250,251], filter and Kraft paper [252][253][254][255], MCC [256][257][258][259][260], sisal [261,262], ramie [263], regenerated cellulose (Lyocell) and cellulose fibres spun from an anisotropic phosphoric acid solution (Bocell) [264], and BC [265]. These studies showed great promise.…”
Section: Applications and New Advances In Cellulose Nanocompositesmentioning
confidence: 99%
“…In the first processing strategy there is a partial or total dissolution of cellulose followed solvent removal, cellulose regeneration of the dissolved part and drying [8,10e13]. The second route relies on cellulose derivatization: a thermoplastic cellulose matrix is simply formed by benzylation [14,15], oxypropylation [16,17] or esterification [18,19]. The etherified or esterified amorphous cellulose derivatives are then hot-pressed with unmodified cellulose to form the ACCs.…”
Section: Introductionmentioning
confidence: 99%
“…Benzylated fibers show the formation of a thermoplastic region surrounding the fiber core [141][142][143][144]. This effectively grafts a thermoplastic polymer matrix onto the outer surfaces of the fibers, with the amount measured by the weight gain [146][147][148]. Fiber volume fractions of up to 40% have been achieved using this method.…”
Section: Benzylated and Oxypropylated Cellulosesmentioning
confidence: 99%
“…The composites are then finally formed by hot pressing [141][142][143][144]. de Menezes [148] et al report that the amorphous regions of the cellulosic materials are more prone to modification than crystalline regions, while the degree of modification is dependent on the amount of PO used [147]. Lu et al reported that the rate of benzylation is not strongly dependent on the wood source, but rather on the amounts of NaOH and benzyl chloride (C 6 H 5 CH 2 Cl), processing temperatures, and reaction times [141][142][143]145].…”
Section: Benzylated and Oxypropylated Cellulosesmentioning
confidence: 99%
See 1 more Smart Citation